ANALISIS PERSEPSI DAN AFEKSI TERHADAP MINAT BELI ONLINE PADA MEDIA SOSIAL FACEBOOK - Helmi, Arief; Fergianti, Farah Dewi (Jurnal Ekonomi dan Bisnis Terapan, 2019)
Facebook has been very popular as a social media, people are also using Facebook as a means to carry out trading activities. This research explores the perceptions and affections of consumers,Â and consumer buying interest in online shopping activities via Facebook social media. The results showed that shopping online through Facebook was not fully considered safe, even though their knowledge of the seller and the products offered were high. The level of consumer confidence in online shopping in terms of payment and shipping is still in the moderate level. But eventough Perceptions and affectionsÂ tend to be high,Â their buying intention to shop on line through Facebook tend to be low. The influence of consumers' perceptions and affections on their buying interest is confirmed by the magnitude of Pearson correlation between perceptions and consumer affections with their buying intention